2019
DOI: 10.1002/cbf.3363
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐β2GPI/β2GPI induces human neutrophils to generate NETs by relying on ROS

Abstract: Neutrophils participate in the regulation of pathogens by phagocytosis as well as by generating neutrophil extracellular traps (NETs). Antiphospholipid antibodies, particularly those targeting beta‐2‐glycoprotein I (β2GPI), stimulate monocytes, platelets, and endothelial cells with prothrombotic participation. This study aimed to explore NET generation in response to anti‐β2GPI/β2GPI. A series of experiments involving the separation of primary human leukocytes, NETosis quantification using propidium iodide, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…In SLE, LDGs are associated with vascular damage (43, 58) and with disease activity in juvenile lupus (59). In APS, LDGs are enriched especially in patients with high titers of anti-β2-glycoprotein-I (60), antibodies capable of inducing NETosis (61, 62).…”
Section: Neutrophils and Their Effector Functions In Sle And Apsmentioning
confidence: 99%
See 1 more Smart Citation
“…In SLE, LDGs are associated with vascular damage (43, 58) and with disease activity in juvenile lupus (59). In APS, LDGs are enriched especially in patients with high titers of anti-β2-glycoprotein-I (60), antibodies capable of inducing NETosis (61, 62).…”
Section: Neutrophils and Their Effector Functions In Sle And Apsmentioning
confidence: 99%
“…Similarly, patients with primary APS also display enhanced spontaneous NET release (62). Plasma of patients with APS (both primary and secondary) as well as aPL alone can induce NETs from healthy neutrophils (61, 138), and NET release correlates with circulating levels of aPL (62). Deposition of NETs can be found in intervillous tissue of pre-eclampsia pregnancies (139), possibly contributing to the pregnancy morbidities present in APS.…”
Section: Neutrophils and Their Effector Functions In Sle And Apsmentioning
confidence: 99%
“…Furthermore, neutrophils from APS patients were shown to display enhanced spontaneous NET release [134,142]. NET response might be mediated through activation of TLR4 [100,142], together with reactive oxygen species (ROS) [100,142,143]. Remarkably, IgG purified from APS patients induced NET release from healthy neutrophils [142].…”
Section: Antiphospholipid Syndrome (Aps)mentioning
confidence: 99%
“…An increase in NET release in response to autoantibodies could be explained by the presence of β2-GP1 on the surface of neutrophils [142]. Several studies observed anti-β2-GP1 to induce NET formation in healthy neutrophils [100,142,143]. Evidences suggest that NETs may directly mediate APS pathology by featuring as a scaffold for platelets to aggregate [144], possibly by presenting a tissue factor [53,100].…”
Section: Antiphospholipid Syndrome (Aps)mentioning
confidence: 99%
“…Furthermore, neutrophils from APS patients were shown to display enhanced spontaneous NET release [134,142]. NET response might be mediated through activation of TLR4 [100,142], together with reactive oxygen species (ROS) [100,142,143]. Remarkably, IgG purified from APS patients induced NET release from healthy neutrophils [142].…”
Section: Antiphospholipid Syndrome (Aps)mentioning
confidence: 99%